Investigating The Need To Redesign Amol's Hefdahe Shahrivar Square With Emphasis On The Promotion Of Functional Components - Kalayi, Ebrahim Amir; Amiri, Niki (The Turkish Online Journal of Design Art and Communication, 2016)
17 Shahrivar square is considered one of the most important squares of Amol, which has four entrances from the streets of Emam Reza, Taleb Amoli, Sheikh Fazlolah Noori and Emam Khomeini. This study has been done with the aim of investigating the physical problems of Amol's 17 Shahrivar square to provide the causes of promoting functional components using its redesign. In this regard, a main and seven sub-hypothesis was considered which consists of (rhythm and balance, statics and dynamics, form and decoration, streets and pedestrian route, human activities, campaigns and social activities). Due to the high volume of population, Cochran's formula of unlimited population is used that the sample size of 196 individuals was selected. Collecting data was done using questionnaire and also books and articles. The SPSS software was used to analyze the data. Results obtained indicate that all components of research are in unfavorable condition and a sever need of redesign is felt in this square.
Keywords: square; redesign; physical problems; functional components